PO:37:256 | Spontaneous renal artery dissection: a subtle presentation of a “vasculitis-mimicker”: Federdo Nogarin1, Alfonso Valerio Massara1, Zairo Ferrante2, Filippo Furicchia3, Riccardo Bertola1, Elena Pollicelli1, Ilaria Calciolari1, Sopie Secka1, Andrea Lo Monaco1, Marcello Govoni1 | 1UOC Reumatologia; 2UOC Radiologia Ospedaliera; 3UOC Radiologia Vascolare e Interventistica, Arcispedale Sant’Anna, Ferrara, Italy (Reumatismo, 2025)
Background. Medium- and large-vessel vasculitides represent a diagnostic challenge. The case described here highlights the importance of an accurate differential diagnosis, as non-inflammatory vascular diseases can mimic vasculitic patterns, with significant therapeutic implications. Materials and Methods. A 42-year-old man presented to the emergency department with subacute onset of temporal headache, low-grade fever, left flank pain, and hypertension (BP 170/100 mmHg). Rheumatologic history was unremarkable and physical examination was normal. Abdominal CT, performed for suspected ureterolithiasis, showed a hypodense area in the mid and upper third of the left kidney compatible with parenchymal ischemia, and a sleeve-like thickening with filiform stenosis of the ipsilateral renal artery, initially suggestive of vasculitis (renal arteritis). The patient was admitted to the Rheumatology Unit. Laboratory tests revealed inflammatory activity (CRP 3.7 mg/dL, ESR 51 mm/h). Intravenous methylprednisolone pulses (250 mg for 3 days) were started, followed by oral prednisone (1 mg/kg) and antihypertensive therapy. Given the suspicion of vasculitis, PET imaging was performed, showing no evidence of vascular inflammation, as well as duplex ultrasound of the four limbs and supra-aortic trunks, which revealed no stenotic or occlusive lesions. Considering the abrupt onset of symptoms, negative autoimmunity, negative PET findings, and absence of additional clinical or instrumental abnormalities, a renal arteriography was performed. It revealed a dissection of the left renal artery with thrombosis of the false lumen and parenchymal ischemia, allowing a final diagnosis of spontaneous left renal artery dissection complicated by renal infarction and renovascular hypertension. Results. The case was discussed with the Radiologist and Vascular Surgeon. Given the complete thrombosis of the false lumen, endovascular revascularization was excluded, and a conservative approach was adopted with antihypertensive and antiplatelet therapy, along with progressive steroid tapering, with no clinical relapse. A follow-up contrast-enhanced CT after 15 days confirmed stability of the renal ischemic lesion and improved parenchymal perfusion (Figure 1). Conclusions. Spontaneous renal artery dissection is a rare clinical entity with elusive etiology, accounting for only 1–2% of all arterial dissections. To date, approximately 200 cases have been reported in the medical literature. Our case emphasizes the importance of considering non-inflammatory vascular conditions, such as spontaneous dissection, in all instances where first-line imaging raises a generic suspicion of medium- or large-vessel vasculitis, particularly in cases of isolated vascular involvement and absence of systemic symptoms. A high index of suspicion is required in clinical practice, especially in atypical or subtle presentations, to promptly achieve the correct diagnosis.